2001
DOI: 10.1149/1.1354615
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Mechanism of Corrosion Inhibition by Polyaniline. Polyaniline-Coated Stainless Steel in Sulfuric Acid Solution

Abstract: The objective of this work was to elucidate the mechanism by which polyaniline ͑PANI͒ films passivate stainless steel surfaces in highly corrosive H 2 SO 4 solution. A variety of experimental methods, including measurements of the open-circuit potential, Auger depth profiling, and the scanning reference electrode technique ͑SRET͒, was used. These studies have shown that passivation is achieved because the oxidized and protically doped emeraldine-salt form of PANI holds the potential of the underlying stainless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…The oxalate system was used to electrodeposit polyaniline at iron, while the sulphate medium was used in the electroformation of the polymer at the platinum electrodes. The electrochemical activity and anodic polarization measurements were carried out in alkaline pH 10 Electrochemical experiments were carried out using an EG&G Potentiostat, Model 263, a Solartron 1250 frequency response analyser and a Solartron EI 1287 electrochemical interface. The polymers were formed using potential cycling at a scan rate of 10 mV s À 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxalate system was used to electrodeposit polyaniline at iron, while the sulphate medium was used in the electroformation of the polymer at the platinum electrodes. The electrochemical activity and anodic polarization measurements were carried out in alkaline pH 10 Electrochemical experiments were carried out using an EG&G Potentiostat, Model 263, a Solartron 1250 frequency response analyser and a Solartron EI 1287 electrochemical interface. The polymers were formed using potential cycling at a scan rate of 10 mV s À 1 .…”
Section: Methodsmentioning
confidence: 99%
“…These conducting properties enable oxidation and passivation of the substrate. Indeed, Kinlen et al [9] have shown, using a scanning vibrating reference electrode technique that doped polyaniline induces the passivation of steel at pinhole defects in the coating, while Gašparac and Martin [10] have concluded that polyaniline coatings induce passivation of a stainless steel surface even though the surface is not completely coated with the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing competitive price of stainless steel could add to its advantages over the usage of other forms of steels. According to several authors, the excellent corrosion resistance of stainless steel in many aqueous solution results from its ability to protect itself from the corrosive environment via formation of a thin passive film [3]- [7] which consists of a mixture of iron and chromium oxides, with the hydroxide and watercontaining compounds located at the outermost region of the passive film while the chromium oxide enrichment is found at the metal/film interface [8]. This film varies in composition from alloy to alloy and also temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…1) He reported that stainless steel covered by PANI layer was kept passive state in sulfuric acid solution for long time period. Other authors also presented the corrosion prevention of stainless steel by PANI coating [2][3][4] as well as PPy coating. 5,6) Since the conducting polymer coatings could be electrochemically formed on various metals, 7,8) they were applied to corrosion prevention of the metals of Cu, 9) Zn, 10) Al, 11) Ti, 12) CuNi.…”
Section: Introductionmentioning
confidence: 99%